From the marginality of the 1960s to the new poverty of today: A LARR research forum - Gonzalez de la Rocha, Mercedes
This paper derives from a LARR-sponsored forum at the LASA 2003 Congress held in Dallas in Mach 2003. Targeted at younger scholars, a panel of leading researchers whose early work was shaped by marginality and dependency thinking of the 1960s were invited to reflect cross-generationally about how paradigms analyzing poverty in Latin American cities have shifted from that time to present